Community Service in Promotive and Preventive Efforts for Hypertension in the Ciceri Permai IV Complex, Serang Banten - Azizan Umi Hamilda; Tri Wahyuni Sukesi (ABDIMAYUDA: Indonesia Journal of Community Empowerment for Health, 2022)
Hypertension is a disease that is a national health problem. The incidence of hypertension is quite high which is caused by an unhealthy lifestyle. Based on the 2018 Riskesdas, the prevalence of hypertension in Indonesia in the population aged 18 years is 34.1%, it is known that 8.36% have been diagnosed with hypertension and 32.27% do not take medicine regularly and 13.33% do not take medicine. Based on a survey at the Ciceri Permai IV Complex, public awareness is still lacking for routine blood pressure checks and lack of awareness to routinely take hypertension medication for those who have been diagnosed with hypertension. This community service aimed to increase knowledge and awareness of hypertension prevention. The method used is community diagnostics to find out the main health problems, followed by counseling methods to solve the main problems. The location of this community service was carried out at RT 02 Ciceri Permai IV Complex, Serang District, Serang Regency, Banten. Community service will be held on April 28 – May 09, 2021 with a team consisting of 2 people, 1 lecturer and 1 student. Based on the community diagnostic, it is shown that hypertension is a major problem, the level of adherence to taking medication and routine blood pressure checks is still low. To overcome these problems, interventions were carried out in the form of counseling, checking blood pressure, providing blood pressure measuring devices and installing hypertension prevention posters in strategic locations. Based on the results of the Wilcoxon test, it showed p value = 0.03 meaning that there was a significant difference in the average knowledge before and after the intervention. Public knowledge and awareness in the effort to prevent hypertension can be increased by this community service activity. The community was also enthusiastic about checking blood pressure independently with the tools that have been provided.